A new species of Lusius (Hymenoptera: Ichneumonidae) from New Zealand. Issue 2 (3rd July 2017) - Saunders, Thomas E.; Ward, Darren F.
ABSTRACT: Lusius malfoyi n. sp. (Hymenoptera: Ichneumonidae) is described. It is an endemic New Zealand species and the first species of the genus to be described from the Australasian region. Zoobank.org:pub:21DCEA3E-C32B-4915-A02B-0212A35E496D